ANALISIS ALIH KODE DAN CAMPUR KODE PADA TUTURAN ACARA INI TALK SHOW DI YOUTUBE - Ramdani Ramdani; Rochmat Tri Sudrajat; Yeni Rostikawati (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research discusses the problems of Code Switching and Code Mixing that occur in the speech title speech in Ini Talk Show. The purpose of this research was to describe the form of Code Switching and Code Mixing performed by speakers at the event. The method used by Researchers in this research is a descriptive qualitative method. In this Research, The role of The researcher is an instrument and data collector. The data collection technique is done by observing, listening, and taking notes. The results of the research found that code-switching and code-mixing were carried out by speakers at the event. Researchers found the Switching of Codes Internal from Indonesian into Sundanese. Switching of Codes External from Indonesian into English, English into Indonesian, Indonesian into Arabic, and from English into Javanese. Whereas Mix code researchers found in the form of words, phrases, baster, and clause. Factors that cause Code Switching are motivated by speakers, interlocutors, the presence of a third person, and to generate a sense of humor. Meanwhile, code-mixing is motivated by the language of the speaker and interlocutor, and tries to interpret or explain.